WATER QUALITY AND RESIDUALS OF NITRATE - NITRITE IN SOME VEGETABLE PLANTED IN CEMETERY AT THANH TRI DISTRICT, HANOI, VIETNAM - Xuan Dung, Bui; Thuy Quynh, Kieu; Thi My Linh, Nguyen; Thi Thu Phuc, Do (Journal of Forestry Science and Technology, 2019)
Vinh Quynh commune, Thanh Tri district, Hanoi is well-known for one of the places that provides a lot of vegetables for Hanoi people, but the vegetables growing near the cemetery area contain numerous of hidden risks. To assess water quality and the residuals of nitrate and nitrite contents in three types of vegetables: Ipomoea aquatic, Nasturtium officinale, and Oenanthe javanica, the study took 12 surface water samples to analyze pH, TSS, COD, NO2-, Fe, NH4+, PO43- and NO3- and 10 groundwater samples for analyzing pH, Fe, NO2-, PO43- and NO3-. In addition, 16 vegetable samples (10 samples of water spinach, 3 samples of watercress, and 3 samples of water dropwort) were collected to analyze nitrate and nitrite concentration in vegetables by a method of extraction and chemical color. The main results of the study included: (1) The surface water was polluted in Fe, PO43-, NO2-, NH4+, COD, TSS and NO3- whereas groundwater was polluted in 4 indicators: Fe, PO43-, NO2-, and NO3-. Especially, NO3- and PO43- had the highest concentration which exceeded 18 times permitted level for surface water sample nearest distance to the cemetery. The WQI index of groundwater was very poor at 208.5. Pollution of groundwater may be due to the infiltration of pollution sources from surface water. Typically, the correlation index of NO3- concentration in surface water and fresh water is very high (r = 0.972); (2) All types of vegetables had NO3- concentration exceeded the permitted levels of WHO and EC. Vegetable sample located nearest the cemetery had the highest NO3- contents were 742 and 728 mg/fresh-kg, surpassed 2.5 times the safe level, respectively.